2001
DOI: 10.1023/a:1011183421477
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor expression in 780 breast cancer patients: A reappraisal of the prognostic value based on an eight-year median follow-up

Abstract: EGFR determination is of limited value as a prognostic indicator in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 25 publications
6
40
1
Order By: Relevance
“…It should also be mentioned that we have analyzed EGFR and AIB1 on tissue microarray, which in a study by Henriksen and co-workers were comparable to the analyses on whole sections [22]. EGFR has been found to be associated with an aggressive tumour type having prognostic value in clinical studies, including cohorts of patients treated with adjuvant chemotherapy [23][24][25]. Tsutsui and co-workers showed that patients with high EGFR and negative ER had the worst prognosis, at least in univariate analysis [24].…”
Section: Discussionmentioning
confidence: 58%
“…It should also be mentioned that we have analyzed EGFR and AIB1 on tissue microarray, which in a study by Henriksen and co-workers were comparable to the analyses on whole sections [22]. EGFR has been found to be associated with an aggressive tumour type having prognostic value in clinical studies, including cohorts of patients treated with adjuvant chemotherapy [23][24][25]. Tsutsui and co-workers showed that patients with high EGFR and negative ER had the worst prognosis, at least in univariate analysis [24].…”
Section: Discussionmentioning
confidence: 58%
“…For example, deregulation of epidermal growth factor receptor (EGFR) activation has been shown to be closely associated with head and neck and breast cancers (1)(2)(3)(4)(5). The EGFR is one of a family of four closely related receptors: EGFR (erbB1), HER2/neu (erbB2), HER3 (erbB3), and HER4 (erbB4), (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR overexpression has been associated with oestrogen receptor (ER) and progesterone receptor (PR) negativity (Pawlowski et al, 2000;Ferrero et al, 2001;Tsutsui et al, 2002;Bieche et al, 2003). Moreover, there may be an association between EGFR positivity and high histological grade or lymph node involvement, although not all existing studies are in agreement (Pawlowski et al, 2000;Ferrero et al, 2001;Witton et al, 2003;Rampaul et al, 2004;Tzaida et al, 2007). Currently, the prognostic significance of EGFR in breast cancer patients remains unclear.…”
mentioning
confidence: 99%